Modes of staff development [videorecording] (SEAMEO INNOTECH, 1990)
Demonstrated the various modes to upgrade school head instructional and management/leadership skills. Describes the steps involved in starting and/or reviewing different modes of staff development specifically to enable school heads to help improve the personal and professional development of their teachers.